2021
DOI: 10.3390/jcm10030511
|View full text |Cite
|
Sign up to set email alerts
|

Loop-Mediated Isothermal Amplification in Schistosomiasis

Abstract: Human schistosomiasis is one of the most important parasitic diseases, causing around 250 million cases (mostly in Africa) and 280,000–500,000 deaths every year. Due to the limited resources and the far-removed nature of many endemic areas, the implementation of new, sensitive and specific diagnostic tools has had little success. This is particularly true for PCR-based molecular methods that require expensive equipment and trained personnel to be executed. Loop-mediated isothermal amplification (LAMP) along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…The LAMP technique, which uses isothermal conditions to amplify DNA, is relatively simple, cost-effective, rapid, and more field-friendly compared with commonly used PCR-based methods [ 51 , 112 ]. Isothermal amplification does not require specific equipment, such as a thermocycler, electrophoresis apparatus, UV transilluminator, etc., while only a heating block or hot water bath is required for the reaction to progress [ 83 , 113 , 114 ]. The amplification results can be judged by precipitation turbidity of magnesium pyrophosphate or color reaction with the naked eye [ 115 ].…”
Section: Molecular Methods Developed To Detect the Pathogen Of Schist...mentioning
confidence: 99%
See 2 more Smart Citations
“…The LAMP technique, which uses isothermal conditions to amplify DNA, is relatively simple, cost-effective, rapid, and more field-friendly compared with commonly used PCR-based methods [ 51 , 112 ]. Isothermal amplification does not require specific equipment, such as a thermocycler, electrophoresis apparatus, UV transilluminator, etc., while only a heating block or hot water bath is required for the reaction to progress [ 83 , 113 , 114 ]. The amplification results can be judged by precipitation turbidity of magnesium pyrophosphate or color reaction with the naked eye [ 115 ].…”
Section: Molecular Methods Developed To Detect the Pathogen Of Schist...mentioning
confidence: 99%
“…Hence, it is more suitable in resource-poor settings and grass-roots units. In addition, the four specific primers designed for six regions of target genes make the assay highly specific [ 113 , 114 ]. Of course, the LAMP technique has some shortcomings that need to be improved.…”
Section: Molecular Methods Developed To Detect the Pathogen Of Schist...mentioning
confidence: 99%
See 1 more Smart Citation
“…NAATs have also demonstrated to be very useful for detection and strain typing of hybrid schistosome infections (3). To overcome the need for expensive laboratory equipment and highly trained personnel, more field-friendly alternatives have been developed, such as for example loopmediated isothermal amplification (LAMP) (64,65) and recombinase polymerase amplification (RPA) (6,66), although both need further validation.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…Improved coprological tests, such as the saline gradient method ( Coelho et al, 2009 ), formalin-ethyl acetate sedimentation-digestion (FEA-SD) ( Xu et al, 2012 ), and the Helmintex method (a procedure that isolates eggs from fecal samples with the use of paramagnetic particles in a magnetic field) ( Lindholz et al, 2018 ), showed increased diagnostic sensitivity compared with the traditional techniques; on the down side, these procedures are usually labor-intensive, and have a lengthy processing time. Molecular methods based on polymerase chain reaction (PCR) technology, including real-time quantitative (q)PCR ( Cnops et al, 2013 ; Gordon et al, 2015 ; Magalhaes et al, 2020 ; Mu et al, 2020 ; Halili et al, 2021 ), loop-mediated isothermal amplification (LAMP) ( Gandasegui et al, 2015 , 2018 ; Garcia-Bernalt Diego et al, 2021 ), and droplet digital (dd) PCR-based tests ( Weerakoon et al, 2016 , 2017a , b ), are alternatives for schistosomiasis surveillance due to their exceptional diagnostic performance; however, these tests are expensive (e.g., the high price of DNA extraction, qPCR assay reagents, and equipment), and require experienced human resources, making their implementation in resource-limited areas challenging.…”
Section: Introductionmentioning
confidence: 99%